Characterization of Honey from Marigat in Baringo County, Kenya, based on their Physical Properties - Chepkemoi, M.; Kollongei, J.; Some, D. (Africa Environmental Review Journal, 2021)
Marigat in Baringo County is among the Arid and Semi-arid Lands (ASAL) in Kenya where apiculture is the main source of income. Honey producers in the area keep their bees in the indigenous hives and natural colonies. Traditional methods are mainly used to harvest and process honey in the area. Honeycombs are crushed and mashed with bare hands to produce honey which is very unhygienic and not fit for human consumption. Honey produced by this method is of low quality hence sold in the local markets at a very low price. This contributes to high poverty levels and low living standards of honey producers residing in the area. However, this paper aims at characterizing honey based on its physical properties. These properties are significant in providing information regarding the quality of honey harvested from different locations of Marigat. This paper presents the physical properties of twelve (12) samples of honey collected from various locations of Marigat. The locations were Maoi Centre, Lopoi Junction, Marigat Town, and Koriema Centre. Honey samples from these locations were analysed based on their physical properties to determine the quality of honey produced in the area. The physical properties were moisture content, pH, relative density, and total water-insoluble solids content. Values of these parameters were compared with those of the set standards and requirements by the Kenya Bureau of Standards (KEBS) in Kisumu County. Results showed mean parameter values of moisture content, pH, relative density and total water-insoluble solids content of 18.05%, 3.9, 1.41 g/ml, and 0.22% m/m respectively. The range values of these parameters were 17.1% to 19.6%, 3.3 to 4.2, 1.4045 g/ml to 1.4343 g/ml, and 0.07% m/m to 0.61% m/m respectively. Moisture content and total water-insoluble solids content values of honey samples were within the maximum requirements of 22% and 0.5% m/m respectively as set by KEBS. However, results obtained from some locations for moisture content were not within the range of 14 to 18% as set by International Honey Commission (IHC) and Codex Alimentarius Commission (CAC). The total water-insoluble solids content of honey proved that honey was extracted by using the traditional method. The relative density of honey was slightly lower and higher than the set permitted limit of 1.42 g/ml, showing that moisture content in honey may be present in some locations. The pH values of honey were observed to be slightly higher and lower in some locations than the recommended value of 3.9. Hence, determining the quality of honey would ensure honey produced meets both local and international standards. This will attract higher profits and increased production rates. Hence, improving the standards of living of honey producers living in the area due to increased income from the sale of honey.